OPTIMIZING LEARNING ENVIRONMENTS: A LITERATURE REVIEW ON MICROSERVICES FOR MOODLE QUALITY IMPROVEMENT - Muhdiantini, Cindy; Amril, Salsabila Zahrani; Prayoga, Danar; Nurdin, Ali; Paramita, Paramita; Lubis, Muharman (STKIP PGRI Tulungagung, 2024)
This paper explores the optimization of Moodle, an open-source learning management system, with a focus on the role of its architecture in improving quality and functionality. Architectural innovation was emphasized as critical to improving the quality of Moodle, with its open-source nature enabling community involvement to improve resolution, security, and evaluation. Moodle is an open-source learning management system (LMS) designed to provide an online learning environment. This research uses a literature review method to collect data from previous studies and literature related to Architectural Innovation and its relationship with academic information systems, namely Moodle. The review introduces the concept of microservices as a potential solution to overcome challenges in content, interface, navigation and technical aspects. Microservices offer independent development opportunities, address usability issues and improve responsiveness. The conclusion highlights that implementing microservices in Moodle not only promises to improve quality but also provides a foundation for meeting the evolving and dynamic needs of users.